Merton's Last Talk and the New Monasticism as Calligraphy in the Twenty-First-Century World - Murphy, Ed (The Merton annual, 2025)
The day of his death, Thomas Merton delivered his final talk, "Marxism and Monastic Perspectives." While it was overshadowed by the tragedy that followed, this talk contains many messages that are relevant today and it challenges us to critically engage with our place in the twenty-first-century world. In it, Merton discussed the similarities and distinctions between Marxism and monastic ideals, the stance of student revolutionaries and the possibilities of living monastic values without institutions or monasteries. This article explores those ideas, highlighting their relevance to the new monasticism. It highlights one co-author's personal experiences emerging from the Vietnam War, and taking up "a critical attitude toward the world and its structures" which Merton suggested was the essence of the monastic. Using the metaphor of calligraphy, the article presents a variety of examples of new monastic communities across the world.